Self-regulated dual-mode solar energy harvesting - Raphael Kay; Rafiq Omair; Joanna Aizenberg (Proceedings of the National Academy of Sciences, 2026)
Traditional solar energy harvesters are single-mode—typically designed to convert available sunlight either into heat or electricity. However, neither energy form is continuously useful, and an optimal variant should instead be capable of autonomously toggling relative thermal and electrical yield based on need. Here, we introduce passive, dual-mode indoor solar energy harvesting by using a fluid layer trapped above a Fresnel lens as a phase-changing switch within a solar waveguide. When warm out and electricity is desired, the fluid is in its vapor phase, causing a refractive index difference with the microstructured lens beneath it to concentrate sunlight toward a solar cell. When cold out and heat is instead desired, the fluid condenses atop the Fresnel structure to reduce refractive index differences, causing sunlight to refract past the solar cell and convert to heat when absorbed indoors. Using water as a phase-changing switch, we built an exemplary system that self-regulates indoor temperature and solar cell light exposure over ambient heating and cooling cycles. Our approach is general across everyday materials and manufacturing methods and may be deployed on the surfaces of vehicles, greenhouses, and residential or commercial buildings.